Greeks in Ptolemaic Egypt: inter-cultural influences in Naukratis - Payne, Simon W. (My University, 2012)
This study analyzes the interactions between Greek colonists and native Egyptians at the site of Naukratis through the material remains found there. Initial excavations by Petrie and Gardener are discussed as well as recent ones by Coulson and Leonard. This study aims to understand any change in material use of household goods by the Egyptians and Greeks living in the city by comparing them to a paradigm of typical Egyptian goods at the time.
Keywords: Naukratis (Extinct city); Creece -- Antiquities.; Egypt -- Antiquities.; Excavations (Archaeology) -- Eqypt.; Archaeology and history.; Archaeology -- Methodology.